2015
DOI: 10.1016/j.bbr.2015.05.046
|View full text |Cite
|
Sign up to set email alerts
|

The common neural parasite Pseudoloma neurophilia is associated with altered startle response habituation in adult zebrafish (Danio rerio): Implications for the zebrafish as a model organism

Abstract: The zebrafish’s potential as a model for human neurobehavioral research appears nearly limitless despite its relatively recent emergence as an experimental organism. Since the zebrafish has only been part of the research community for a handful of decades, pathogens from its commercial origins continue to plague laboratory stocks. One such pathogen is Pseudoloma neurophilia, a common microparasite in zebrafish laboratories world-wide that generally produces subclinical infections. Given its high prevalence, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 45 publications
(70 reference statements)
0
41
0
Order By: Relevance
“…In addition, we provide an example of a natural infection associated with clinical disease in a population of laboratory fish, P. promelas. Previous studies have demonstrated the impact of P. neurophilia on zebrafish on common research endpoints such as behavior 19 and fecundity. 20 Similar studies need to be performed on other fish species to determine the impact of nonprotocol-induced variation due to subclinical P. neurophilia infection when they are used in research.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we provide an example of a natural infection associated with clinical disease in a population of laboratory fish, P. promelas. Previous studies have demonstrated the impact of P. neurophilia on zebrafish on common research endpoints such as behavior 19 and fecundity. 20 Similar studies need to be performed on other fish species to determine the impact of nonprotocol-induced variation due to subclinical P. neurophilia infection when they are used in research.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 For example, a recent study indicated that background infections could impact zebrafish behavior. 7 One of the most tangible benefits is increased insurance against a catastrophic colony loss due to a virulent pathogenic outbreak. Although the number of serious pathogens affecting zebrafish continues to increase, diagnostic technology has advanced to the point that there is no longer an excuse to not stay on top of it.…”
Section: Discussionmentioning
confidence: 99%
“…More commonly, it is associated with reduced growth and decreased reproductive fitness. 18 Infection with this organism was recently shown to alter behavioral testing conducted with infected fry, 19 and intramuscular granuloma development and myonecrosis associated with infection may display autofluorescence interfering with imaging studies. 20 This agent can be vertically as well as horizontally transmitted, and most currently used protocols for embryo surface disinfection with sodium hypochlorite do not prevent horizontal transmission to offspring.…”
Section: Choice Of Agentsmentioning
confidence: 99%